2010
DOI: 10.1007/s11998-010-9247-4
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of novel photosensitive polysiloxanes and their effects on properties of UV-cured epoxy methacrylate coatings

Abstract: Two UV-curable polysiloxanes-side methacryloxy group polysiloxanes (MAPS) -were successfully synthesized through a two-step reaction. Two series of various percentages of these synthesized MAPS were then cured with bisphenol-A epoxy methacrylate (BEMA) via UV radiation to obtain cured coatings. We found that the additive MAPS improved the thermal stability of the cured coatings. It not only reduced the surface energy of the coatings, but also significantly affected the other properties, including gloss, flexib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Photopolymers, mainly composed of multifunctional monomers, oligomers, and photoinitiators, are responsible for the properties of the printed objects . The main requirements for photopolymers used in 3D printing involve high curing rate, good storage stability, low viscosity, low toxicity, and good mechanical property after curing …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photopolymers, mainly composed of multifunctional monomers, oligomers, and photoinitiators, are responsible for the properties of the printed objects . The main requirements for photopolymers used in 3D printing involve high curing rate, good storage stability, low viscosity, low toxicity, and good mechanical property after curing …”
Section: Introductionmentioning
confidence: 99%
“…Crivello et al have reported that silicone–epoxy resins have higher photocuring rate than that of aliphatic epoxy, and even higher than common cycloaliphatic epoxy resins . Furthermore, the cured resins may have small stress and good toughness due to the introduction of organic silicone chain segment …”
Section: Introductionmentioning
confidence: 99%
“…Siliconcontaining materials have peculiar characteristics such as thermal stability, 9,10 weathering resistance, 11,12 flexibility 13 , and water impermeability, 14 and they have been used in various applications including high-performance elastomers, membranes, adhesives, antifoams, electrical insulators, water repellants, fire retardants, textile softeners, medical materials and coupling agents. [15][16][17] There are three types of usual strategies to incorporate silicon into hybrid UV-cured systems in previous studies: (1) mixing silicon dioxide (SiO 2 )/polysiloxane with some photopolymerization oligomer to form inorganic-organic hybrid systems 9,18 ; (2) preparing silicon-containing acrylates by Michael-type addition reaction between polysiloxane and acrylate for free-radical photopolymerization [19][20][21] ; and (3) preparing silicon-containing epoxide or vinyl ether by hydrosilation reaction between polysiloxane and epoxide/vinyl ether for cationic photopolymerization. 13,[22][23][24] However, most of these techniques are not suited to practical application because the step-by-step syntheses of silicon-containing oligomers restrict industrial production on a large scale.…”
Section: Introductionmentioning
confidence: 99%